Laser fetal surgery in feto-fetal transfusion syndrome and selective intrauterine fetal growth restriction - Molina-Giraldo, Saulo (2018)
Introduction: The monochorionic biamniotic twin pregnancy (MCBA) corresponds to approximately 15% of all twin pregnancies and an estimate of 10-15% develop complications proper of these types of pregnancies, such as selective intrauterine fetal growth restriction (IUGRs) and feto-fetal transfusion syndrome (FFTS). Laser fetal surgery allows treatment of these hemodynamic alterations of MCBA by fulguration of placental anastomoses, and it is currently considered the first-choice therapy for FFTS and some IUGR cases. Objectives: To highlight the general aspects of laser fetal surgery and to describe current evidence of its efficacy and safety in FFTS and IUGRs. Methods: Review of articles published during the last five years in indexed journals from the following databases: PUBMED, MEDLINE, EMBASE and Cochrane Library. Review papers, original papers, and systemic reviews were included. Classic relevant papers on fetal surgery history were also included. Results: By means of this nonsystematic review of the literature, 43 articles were considered for the present paper. Conclusion: This review evidences that laser fetal surgery improves the prognosis of FFTS fetuses. The use of this therapy in IUGRs cases has not improved survival.